1993
DOI: 10.1021/bi00065a009
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of G.cntdot.A and A.cntdot.A pairing in (dGCGAATAAGCG)2

Abstract: One- and two-dimensional NMR, UV absorption experiments, and molecular mechanics calculations were conducted on an oligonucleotide duplex (dGCGAATAAGCG)2 which will be referred to as the T-11-mer. This oligonucleotide forms a duplex that is primarily B-form and contains two adjacent G.A and A.A base pairs and two 3' unpaired guanosines. The adjacent mismatch base pairs have an unusual structure which includes overwinding the helix and stacking with the base from the complementary strand (A4 with A8 and G3 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
49
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 67 publications
8
49
1
Order By: Relevance
“…In simple PyGAPu contexts with no intervening nucleotide, directly adjacent GÁ A and A Á G pairs form rather stable sheared (GA) 2 motifs. Similar stable PyGAPu:PyAAPu motifs with tandem sheared GÁA and AÁA pairs have been reported (Maskos et al, 1993).…”
Section: Resultssupporting
confidence: 80%
“…In simple PyGAPu contexts with no intervening nucleotide, directly adjacent GÁ A and A Á G pairs form rather stable sheared (GA) 2 motifs. Similar stable PyGAPu:PyAAPu motifs with tandem sheared GÁA and AÁA pairs have been reported (Maskos et al, 1993).…”
Section: Resultssupporting
confidence: 80%
“…144 Structure 8 involves a protonated adenine forming a base pair with an unprotonated adenine, as reported for a DNA duplex. 145,146 Structure 9 involves protonated adenine engaged in Hoogsteen pairing with guanine, as reported for a DNA duplex. 146 backbone, it does offer the possibility for the existence of local regions with enormous negative surface potential.…”
mentioning
confidence: 86%
“…145,146 Structure 9 involves protonated adenine engaged in Hoogsteen pairing with guanine, as reported for a DNA duplex. 146 backbone, it does offer the possibility for the existence of local regions with enormous negative surface potential. Indeed, nonlinear Poisson-Boltzmann (NLPB) calculations have revealed a number of such regions in RNAs with tertiary structure, and several of these regions have been shown to correlate with Mg 2ϩ binding sites.…”
mentioning
confidence: 86%
“…GÁA mismatches in the socalled sheared base-pair con®guration, in which both nucleotides are in the anti conformation, and in which hydrogen bonds are formed between the guanine 2-amino to the adenine N7 and the guanine N3 to the adenine 6-amino were originally found in a DNA duplex (Li et al, 1991) and an RNA hairpin loop (Heus & Pardi, 1991), and have been observed in RNA at loop helix junctions (Szewczak et al, 1993;Szewczak & Moore, 1995;Biou et al, 1994;Pley et al, 1994a,b;Scott et al, 1995;Cate et al, 1996;Huang et al, 1996;Fountain et al, 1996;Jucker et al, 1996), within internal loops in RNA (SantaLucia & Turner, 1993;Katahari et al, 1994;Szewczak et al, 1993;Szewczak & Moore, 1995) as well as in DNA (Chou et al, 192;Lane et al, 1992;Katahari et al, 1993;Ebel et al, 1994;Maskos et al, 1993). Thermodynamic studies have revealed that the stabilities of tandem GÁA basepairs in RNA can range over almost 5 kcal mol À1 , depending on the closing base-pair (Walter et al, 1994).…”
Section: Introductionmentioning
confidence: 98%